Infection Prevention and Control at Lira University Hospital, Uganda: More Needs to Be Done - Opollo, Marc Sam; Otim, Tom Charles; Kizito, Walter; Thekkur, Pruthu; Kumar, Ajay M. V.; Kitutu, Freddy Eric; Kisame, Rogers; Zolfo, Maria (Tropical Medicine & Infection Disease, 2021)
Globally, 5–15% of hospitalized patients acquire infections (often caused by antimicrobialresistant microbes) due to inadequate infection prevention and control (IPC) measures. We used the World Health Organization’s (WHO) ‘Infection Prevention and Control Assessment Framework’ (IPCAF) tool to assess the IPC compliance at Lira University hospital (LUH), a teaching hospital in Uganda. We also characterized challenges in completing the tool. This was a hospital-based, crosssectional study conducted in November 2020. The IPC focal person at LUH completed the WHO IPCAF tool. Responses were validated, scored, and interpreted per WHO guidelines. The overall IPC compliance score at LUH was 225/800 (28.5%), implying a basic IPC compliance level. There was no IPC committee, no IPC team, and no budgets. Training was rarely or never conducted. There was no surveillance system and no monitoring/audit of IPC activities. Bed capacity, water, electricity, and disposal of hospital waste were adequate. Disposables and personal protective equipment were not available in appropriate quantities. Major challenges in completing the IPCAF tool were related to the detailed questions requiring repeated consultation with other hospital stakeholders and the long time it took to complete the tool. IPC compliance at LUH was not optimal. The gaps identified need to be addressed urgently.
Keywords: Core components of infection prevention and control; Healthcare-associated infections; Operational research; SORT IT (Structured Operational Research and Training Initiative); Low-income and middle-income countries